KOLABORASI DAN SINERGI ANTAR LEMBAGA DALAM PENINGKATAN KOMPETENSI KEPALA SEKOLAH - Wasitohadi Wasitohadi (Kelola: Jurnal Manajemen Pendidikan, 2016)
Collaboration and synergy among institutions in enhancing principal’s competence is very essential. This may cover many areas, from recruitment-including the system of selection-, until certification for principal, principal candidate’s training, and capacity building for principal. Optimizing role of each institutions and the parties which are involved in a collaborative and synergistic way in accordance with the systems and mechanisms, will determine the competence of the principal. This collaboration and synergy will create qualified principal according the demands and needs of autonomy in MEA era.